Fundamentals of geomorphology - Huggett, Richard J. (Routledge fundamentals of physical geography series., 2011)
Fundamentals of Geomorphology provides a stimulating and innovative perspective on the key topics and debates within the field of geomorphology. Written in an accessible and lively manner, it includes guides to further reading, chapter summaries, and an extensive glossary of key terms. The book is also illustrated throughout with over 200 informative diagrams and attractive photographs, all in colour. --Book Jacket.